The Development of Butterfly pea (Clitoria ternatea) Flower Powder Drink by Co-crystallization - Marpaung, Abdullah Muzi; Lee, Michael; Kartawiria, Irvan Setiadi (Department of Technology of Agricultural product (THP) Jambi University, 2020)
Abstract— A method consist of co-crystallization, agglomeration, drying has been applied to develop a powder drink from butterfly pea flower (Clitoria ternatea) extract. The butterfly pea flower extract was concentrated by vacuum evaporation and incorporated with supersaturated sugar solution (more than 90 Brix), agglomerated and dried at 60oC for 12 hours. The anthocyanin stability and antioxidant activity of the powder drink was evaluated for 28 days at three levels of temperature (room temperature, 40oC, and 50oC). The stability of anthocyanin decreased as the increase of storage temperature. The half-life of anthocyanin in the powder drink at respective temperature was 27.99, 16.53, and 9.81 days. Despite the anthocyanin significantly degraded, the decrease of antioxidant activity of the powder drink was not significant. Hence, the beneficial effect of the butterfly pea powder drink retained. Keywords— anthocyanin; butterfly pea; co-crystallization; stability; sugar